Microscrew implant as an orthodontic anchoring device - Supriadi, Mira Nurtania; Soeria Soemantri, Eky Setiawan; Evangelina, Ida Ayu (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2007)
Microscrew implant is a new alternative of an orthodontic anchoring device which is planted by simple surgery procedure into soft tissue and mandibular bone to utilize mandibular bone as an intraoral anchoring source. Microscrew implant is a small screw and consists of four components that can give various advantages, made from a titanium material, and developed in various sizes and designs. Microscrew implant is strong, stable, and effective to be used as an absolute anchoring device in orthodontic treatment without losing the anchoring.